Pendampingan Desa Cerdas (Smart Village) Melalui Pendataan Demografi, Pemetaan Wilayah, Identitas Desa, dan Website Layanan Desa Karyasari: Pengabdian - Setyo Fiddin Wirabuana; Wita Khaerunisa; Moch. Naufal Fikri Hafizh; Abdul Aziz (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The advancement of digital technology offers significant opportunities for rural areas to transform towards more efficient and inclusive governance. The Smart Village concept emerges as an innovative solution to meet the demands of data-driven, participatory, and sustainable rural development. This community service the implementation of a smart village in Karyasari Village using a participatory approach and descriptive-qualitative methods. The core activities include demographic data collection, spatial-based mapping, visual identity design, and the development of a public service website. Technologies such as GPS, GIS, and web platforms were utilized to accelerate the collection, processing, and presentation of data in an integrated and transparent manner. The results show that the integration of technology and data enhances bureaucratic efficiency, strengthens local identity, and expands public access to village services. This community service that the synergy of technology, data, and community participation is a key foundation for building smart, adaptive, and competitive villages in the digital era.